2011
DOI: 10.1016/j.physa.2011.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Accidental politicians: How randomly selected legislators can improve parliament efficiency

Abstract: We study a prototypical model of a Parliament with two Parties or two Political Coalitions and we show how the introduction of a variable percentage of randomly selected independent legislators can increase the global efficiency of a Legislature, in terms of both the number of laws passed and the average social welfare obtained. We also analytically find an "efficiency golden rule" which allows to fix the optimal number of legislators to be selected at random after that regular elections have established the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…The latter is a further confirmation that, in complex social and economical contexts where chance plays a relevant role, the efficiency of alternative strategies based on random choices can easily overtake that of standard strategies based on the "naively meritocratic" approach. Such a counterintuitive phenomenon, already observed in management, politics and finance ( [48,49,50,51,52,53,54,55]), finds therefore new evidence also in the research funding context.…”
Section: Serendipity Innovation and Efficient Funding Strategiesmentioning
confidence: 89%
See 1 more Smart Citation
“…The latter is a further confirmation that, in complex social and economical contexts where chance plays a relevant role, the efficiency of alternative strategies based on random choices can easily overtake that of standard strategies based on the "naively meritocratic" approach. Such a counterintuitive phenomenon, already observed in management, politics and finance ( [48,49,50,51,52,53,54,55]), finds therefore new evidence also in the research funding context.…”
Section: Serendipity Innovation and Efficient Funding Strategiesmentioning
confidence: 89%
“…In other words, if luck matters, and if it matters more than we are willing to admit, it is not strange that meritocratic strategies reveal less effective than expected, in particular if we try to evaluate merit ex-post. In previous studies [48,49,50,51,52,53,54,55], there was already a warning against this sort of "naive meritocracy", showing the effectiveness of alternative strategies based on random choices in management, politics and finance. Consistently with such a perspective, the TvL model shows how the minimum level of success of the most talented people can be increased, in a world where luck is important and serendipity is often the cause of important discoveries.…”
Section: Effective Strategies To Counterbalance Luckmentioning
confidence: 99%
“…In fact, in situations of high uncertainty, personal information exchange may reach market-wide impacts, as the examples of bank runs [28] and speculative attacks on national currencies [29] show.Our study explores how huge herding avalanches in financial trading might be reduced by introducing a certain percentage of traders who adopt a random invest-ment strategy. Actually, several analogies between socioeconomic and physical or biological systems have recently been discussed [30][31][32][33], where noise and randomness can have beneficial effects, improving the performance of the system [34][35][36][37][38][39][40][41][42]. More specifically, in a recent series of papers, it has been explored whether the adoption of random strategies may be advantageous in financial trading from an individual point of view.…”
mentioning
confidence: 99%
“…While the idea itself is not new to physics it was just only recently applied to socio-economic systems. E.g., it was shown that random promotions might lead to more efficient hierarchical structures [65] as well as "accidental" politicians potentially improving legislature process [66]. In a couple of more recent publications this idea was applied to the financial markets.…”
Section: Agent-based Herding Model With Controlled Agentsmentioning
confidence: 99%